Media, Culture, And Society: Social Interaction In The Digital Era - A Study Of The Music Community On Tiktok Indonesia - Faqih, Moch. Abdullah; Andari, Lintang Dinar; Novriani , Rinna Ardina (Al-Makki Publisher, 2025)
In the current era of globalization, the development of media technology is taking place very rapidly, giving birth to various digital innovations such as social media. Social media becomes a virtual space that allows individuals to form social networks based on similar interests, activities, and collective identities. One of the platforms that is now the center of digital interaction is TikTok, especially in the music community such as K-Pop, indie, and dangdut. This study uses the theory of symbolic interactionism to understand how individuals in the music community on TikTok shape meaning, identity, and social relationships through symbolic interactions. This theory emphasizes that identity and social reality are not fixed, but are formed through a process of interaction that is loaded with symbols, whether through comments, videos, dance challenges, to collaborative features such as duets and stitches. TikTok is not only a space to express musical preferences, but it is also an arena where social interactions are actively constructed and negotiated. The findings in this study show that participation in the TikTok music community is a form of meaningful communication that shows social connectedness, cultural identification, and digital dynamics in contemporary society.